Biological impact of octyl d-glucopyranoside based surfactants. (February 2019) - Zdarta, Agata; Pacholak, Amanda; Smułek, Wojciech; Zgoła-Grześkowiak, Agnieszka; Ferlin, Nadège; Bil, Abed; Kovensky, José; Grand, Eric; Kaczorek, Ewa
Abstract: Development of many branches of industry has stimulated the search for new, effective surfactants with interesting properties. Potential use of alkyl glucose derivatives on a large scale, raises questions about the possible risks associated with their entry into the natural environment. To be able to evaluate this risk, the aim of the study was to determine the physicochemical properties of octyld -glucopyranoside and its three derivatives: N -(octyld -glucopyranosiduronyl)aspartic acid, N -(octyld -glucopyranosiduronyl)glicyne and octyld -glucopyranosiduronic acid. Moreover, their biodegradability by pure bacterial strains and biocenosis present in river water was examined. While descriptions of sugar-based surfactants on microbial cells are limited, the essential element of the study was to determine the effect of surfactants on cell surface properties of microorganisms isolated from activated sludge and compare it to the effects of the petroleum based surfactants and the surfactants produced from renewable materials. The results obtained indicate that physicochemical properties of surface active agents differ depending on the presence of functional groups in the surfactants molecules. What is more, the presence of amino acid substituent in the derivatives of octyld -glucopyranoside resulted in a slight decrease in the surfactants biodegradation efficiency, in comparison to the compounds that did not contain such a substituent, prolonging this process from 5 to 10 days. Interestingly, even relatively slightly different derivatives modified the cell surface properties in a different way. Importantly, the surfactants based on octyld -glucopyranoside have less negative impact on environmental microorganism and better biodegradability than the surfactant synthesized from petroleum products. Graphical abstract: Highlights: The shown significant surface active properties. The tested surfactants exhibit very good biodegradability by activated sludge bacteria. The octyld -glucopyranoside derivatives modified bacteria cell surface.